PENGARUH DESAIN RUANGAN TERHADAP PERILAKU ANAK JALANAN PADA RUMAH SINGGAH ; STUDI KASUS KAMPUNG ANAK NEGERI - Nadiah Zahrameidina Yusuf; Prasetyo Wahyudie (UNIB Press, 2025)
Shelters act as an important transition space for street children to get protection, coaching, and psychosocial reinforcement. The room's design in the halfway house can affect children's behavior, ranging from emotional aspects to social behavior. This article presents a literature review of various recent studies related to the relationship between spatial design and the behavior of street children in the context of shelters in Indonesia. The study stages are carried out systematically using scientific sources from 2019-2024. The review results found that design elements such as layout, natural lighting, ventilation, color selection, and space flexibility significantly impacted comfort, security, and children's participation in social activities. This study emphasizes the importance of a behavior-based design approach to create spaces that are not only functional but also support the holistic recovery and growth of street children.